PEMBELAJARAN BERBASIS RAMAH ANAK TAMAN KANAK-KANAK DI KECAMATAN BONTOTIRO KABUPATEN BULUKUMBA - Muhammad Yusri Bachtiar (Instruksional, 2020)
The purpose of research on child-friendly learning in kindergarten as follows: 1) to determine the characteristics and needs in the field of child-friendly lerning models in kindergarten, 2) to find out the desgn and practicality of child-friendly learning models in kindergarten, 3) to determine the effectiveness of child-friendly learning models in kindergarten. The type of research used is Research and Development (R&D) by following the Borg and Gall research steps. The location which is the place for researching a child-friendly learning model is kindergarten, Bontotiro sub-district, Bulukumba regency with the characteristic of this model is the management of learning done by teachers is managing learning by applying child-friendly learning models in kindergarten in learning activities have been implemented well. Likewise the good. Anal activity in implementing a child-friendly learning model based on all indicators that exist in the child-friendly learning models is in the high cargoery